Decentralisation and urban primary health services: a case study of Delhi’s Mohalla Clinics (Commonwealth Journal of Local Governance, 2020)
The Indian political party Aam Aadmi, which assumed power in the city-state of Delhi in 2015, introduced Mohalla Clinics (i.e. neighbourhood clinics) to provide free primary health services for all, as a response to the rising inaccessibility of primary healthcare facilities for the urban poor. These clinics were to be governed through Mohalla Sabhas (i.e. neighbourhood committees), which are instruments of participatory governance within the neighbourhood. The research compares promises and practice for Mohalla Clinics, especially focusing on governance and the politics surrounding it. The authors find that in their current form Mohalla Clinics are limited to providing primary curative healthcare and have shown limited success, although Mohalla Clinic users do save time and expenditure on primary healthcare, and the clinics have led to a more comprehensive form of primary healthcare than in the past. However, Mohalla Clinics are governed in a top-down fashion by the Government of the National Capital Territory-Delhi, and not by urban local bodies or the envisaged neighbourhood committees. As a result, they face problems that may inhibit their functioning in the long term.